2019
DOI: 10.12693/aphyspola.135.1290
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Viscosity of Indium Oxide-Ethylene Glycol (In2O3-EG) Nanofluids: An Experimental Investigation

Abstract: Nanofluids, which are suspensions of nanoparticles, are interesting engineering materials, which might find numerous applications in industry. Unfortunately, there is no coherent theoretical model describing viscosity of nanofluids and further experimental and theoretical studies of this issue should be performed. This paper makes a contribution to this field. Dynamic viscosity of ethylene glycol based nanofluids containing indium oxide nanoparticles was measured in shear rate range from 10 s −1 to 1000 s −1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…One of these is the work of Fal et al [21] in which they found an increase in the electrical conductivity of these nanofluids with both concentration and temperature. The maximum increase in electrical conductivity of In 2 O 3 -EG nanofluids, 27 300% was detected for a volume fraction of 0.0081 at 333.15 K. Żyła et al [22] presented the results of an experimental study of the dynamic viscosity of indium oxide nanofluids in ethylene glycol and found that these materials exhibit Newtonian character for each nanoparticle fraction tested. They presented in their results that viscosity increases with nanoparticle fraction, and showed that temperature has a strong influence on the viscosity of these materials.…”
mentioning
confidence: 99%
“…One of these is the work of Fal et al [21] in which they found an increase in the electrical conductivity of these nanofluids with both concentration and temperature. The maximum increase in electrical conductivity of In 2 O 3 -EG nanofluids, 27 300% was detected for a volume fraction of 0.0081 at 333.15 K. Żyła et al [22] presented the results of an experimental study of the dynamic viscosity of indium oxide nanofluids in ethylene glycol and found that these materials exhibit Newtonian character for each nanoparticle fraction tested. They presented in their results that viscosity increases with nanoparticle fraction, and showed that temperature has a strong influence on the viscosity of these materials.…”
mentioning
confidence: 99%